Mycorrhizal type influences plant density dependence and species richness across 15 temperate forests. Issue 3 (11th January 2021) - Jiang, Feng; Lutz, James A.; Guo, Qingxi; Hao, Zhanqing; Wang, Xugao; Gilbert, Gregory S.; Mao, Zikun; Orwig, David A.; Parker, Geoffrey G.; Sang, Weiguo; Liu, Yankun; Tian, Songyan; et al.
Abstract: Recent studies suggest that the mycorrhizal type associated with tree species is an important trait influencing ecological processes such as response to environmental conditions and conspecific negative density dependence (CNDD). However, we lack a general understanding of how tree mycorrhizal type influences CNDD strength and the resulting patterns of species abundance and richness at larger spatial scales. We assessed 305 species across 15 large, stem‐mapped, temperate forest dynamics plots in Northeastern China and North America to explore the relationships between tree mycorrhizal type and CNDD, species abundance, and species richness at a regional scale. Tree species associated with arbuscular mycorrhizal (AM) fungi showed a stronger CNDD and a more positive relationship with species abundance than did tree species associated with ectomycorrhizal (ECM) fungi. For each plot, both basal area and stem abundance of AM tree species was lower than that of ECM tree species, suggesting that AM tree species were rarer than ECM tree species. Finally, ECM tree dominance showed a negative effect on plant richness across plots. These results provide evidence that tree mycorrhizal type plays an important role in influencing CNDD and species richness, highlighting this trait as an important factor in structuring plant communities in temperate forests.